2018
DOI: 10.1055/a-0604-2676
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ultrasound in the Diagnostic Work-Up of Adult Intussusception – A Multicenter Retrospective Analysis

Abstract: US is reliable in the diagnostic work-up of AI when performed by experienced examiners with high-quality equipment. US, CT and MRI should be used in a complementary fashion since combination provides excellent sensitivity regarding the detection and correct localization of AI as well as the detection of complications. The impact of real-time imaging is illustrated by supplementary videos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…We found 8 cases of ileocolic intussusception in infants up to ten months of age, hereof one with necrosis of the intestine. US examinations showing ileocolic intussusception reported typical findings such as "telescoping of bowl into bowl", "doughnut sign" or a "swirl" of the intestines with layers of different echogenicity [33][34][35][36][37][38][39] (fig 1). One case of pediatric intestinal necrosis presented with a significant amount of free intraperitoneal fluid on examination [40].…”
Section: Resultsmentioning
confidence: 99%
“…We found 8 cases of ileocolic intussusception in infants up to ten months of age, hereof one with necrosis of the intestine. US examinations showing ileocolic intussusception reported typical findings such as "telescoping of bowl into bowl", "doughnut sign" or a "swirl" of the intestines with layers of different echogenicity [33][34][35][36][37][38][39] (fig 1). One case of pediatric intestinal necrosis presented with a significant amount of free intraperitoneal fluid on examination [40].…”
Section: Resultsmentioning
confidence: 99%
“…Of the few studies available in the literature, the majority were retrospective analyses and report an accuracy ranging from 60 -85% for ultrasound-detected adult intussusception. [9][10][11] One particular multicentre retrospective analysis reported that abdominal ultrasound was able to correctly localise adult intussusception in 95% of cases and accurately detect complications in 100% of cases. 11 Albeit intussusception is a surgical condition and the patient in this case initially presented to the emergency department, this patient could have developed these symptoms while inpatient on the medicine service.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] One particular multicentre retrospective analysis reported that abdominal ultrasound was able to correctly localise adult intussusception in 95% of cases and accurately detect complications in 100% of cases. 11 Albeit intussusception is a surgical condition and the patient in this case initially presented to the emergency department, this patient could have developed these symptoms while inpatient on the medicine service. When faced with acute changes in a patient's status, vitals, physical examination, and laboratory studies are appropriately first performed.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators reported that ultrasound was found to be less reliable in two adult patient case series and suggested bowel edema, air-fluid levels, and larger fecal loads as potential reasons (30) . However, in a European retrospective multicenter case series, sonographers with 'basic skill sets' detected 63.6% of intussusceptions in adults on initial evaluation, while experts detected 91.7% (31) .…”
Section: Introductionmentioning
confidence: 94%